Early-Onset Adjacent Vertebral Fractures after Balloon Kyphoplasty and SpineJack Kyphoplasty for the Management of Single-Level Thoracolumbar Vertebral Compression Fractures - Chung, Ming-Hsuan; Yang, Yun-Ju; Wu, Yi-Chieh; Chen, Guann-Juh; Ju, Da-Tong; Chou, Kuan-Nien (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background The aim of this study was to evaluate the risk factors contributing to early-onset adjacent level fractures (ALFs) occurring within 1 month following either balloon kyphoplasty (BKP) or SpineJack kyphoplasty (SJ) for the treatment of thoracolumbar vertebral compression fractures (TLVCFs).Methods This retrospective analysis enrolled patients with single-level TLVCFs (T11–L2) who underwent either BKP or SJ between July 2013 and June 2019. We recorded the ALF occurrences within 1 month. Age, osteoporosis, severity and shape of TLVCFs, and surgical type were compared between patients with and without early-onset ALFs.Results Altogether, 106 TLVCF patients were enrolled, comprising 64 BKP and 42 SJ cases. We observed 19 early-onset ALFs, with 9 and 10 cases in the BKP and SJ, respectively. Patients with early-onset ALFs have significantly more severe TLCVFs (severe vs. mild, 25 vs. 0%, p = 0.055), and wedge-shaped TLVCFs (26.47 vs. 2.63%, p = 0.002), older age (81.05 vs. 73.34 years, p < 0.001), and kyphoplasty performed within 1 month are risk factors for early-onset ALFs (26.92 vs. 9.26%, p = 0.018). Univariable analysis showed that kyphoplasty timing within 1 month (odds ratio [OR]: 0.193; p = 0.008), wedge-shaped TLVCFs (OR: 5.358; p = 0.036), and advanced age (OR: 1.119; p = 0.001) are significant risk factors for early-onset ALFs.Conclusions The occurrence rate of early-onset ALFs between BKP or SJ techniques in treating TLVCFs does not differ. Preoperative wedge-shaped TLVCFs, advanced age, and early treatment within 1 month are the risk factors for early-onset ALFs following kyphoplasty for TLVCFs.
Keywords: compression fracture; adjacent fracture; kyphoplasty; osteoporosis